Interculturality and the humanism of diversity: didactic foundations for sustainable education - Ouhtit, Abdelkader; Hammanou, Latifa; Ouhtit, Rachid; Zerhane, Rajae; Janati-Idrissi, Rachid (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2026)
In an era marked by the intensification of human mobility, the issue of interculturality has gained renewed prominence in the field of education. Educational systems are now confronted with increasingly heterogeneous populations, characterized by diverse languages, cultural references, social trajectories, and relationships to knowledge. In this context, intercultural education cannot be reduced to the transmission of descriptive knowledge about “the other” or to a mere pedagogy of tolerance. Rather, it entails the construction of a worldview grounded in the recognition of diversity, critical reflexivity, and the co-construction of meaning within a shared ethical framework. The objective of this article is to demonstrate that interculturality constitutes less a specific field of instruction than a transversal framework of thought, capable of profoundly transforming the aims of education and pedagogical practices.